The Effects of Principal Leadership and Teacher Competence on the Learning Quality: Does the Mediation of Infrastructure Matter? - Kafifahdhi Mukaromah; Wilis Werdiningsih; Rihab Wit Daryono (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Good infrastructure can help teachers in presenting learning materials better. Infrastructure can also assist principals in conducting school administration management more efficiently to focus on developing the quality of learning. This study aims to explore the role of infrastructure as a mediator of the influence of principal leadership and teacher competence on the quality of learning. Method: This study used a quantitative survey of randomly selected 42 teachers at SHS 1 Kawedanan Magetan. Data collection was carried out using a questionnaire consisting of a Likert scale with 5 points. PLS-SEM analysis is used to analyze data and test conceptual models. Data analysis techniques include statistical tests to test relationships and mediation. Results: The results showed that the quality of learning was directly influenced insignificantly by the principal (β=-0.097; ρ=0.522) and teacher competence. Novelty: Infrastructure mediates significantly in improving the quality of learning. Schools and educational institutions must invest time and resources in training and professional development for teachers and principals in leadership, classroom management, and effective teaching methods. The overall quality of learning will improve when the principal can lead the school towards a clear vision of learning, and teachers have adequate skills and knowledge to plan, implement, and evaluate learning effectively.